UNCONSTITUTIONALITY OF THE GENERAL ADMINISTRATIVE PROCEDURE ACT - Cucić, Vuk (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2023)
The Constitutional Court declared the Art. 178(3) of the Law on General Administrative Procedure unconstitutional. This provision sets an objective deadline for reopening of the administrative procedure. The Constitutional Court found that this deadline is unconstitutional when the procedure is reopened as a result of a decision of the Constitutional Court or the ECtHR determining that an administrative act violated a right guaranteed by the Constitution or ECHR. Unfortunately, said provision prescribed an objective deadline for another 10 reasons for reopening of the procedure. By removing it, the Constitutional Court got out of its role of 'negative legislator' and made a legislative choice instead of the legislator, removing parts of the norm that are not inconsistent with the Constitution. When making this decision, the Constitutional Court relied on its previous decisions, which removed the equal provisions on the objective deadline for reopening of the civil litigation and misdemeanor proceedings. The Constitutional Court ignored the fact that this is an administrative procedure and, erroneously, referred to the inconsistency of the pertinent law with the provisions of the Constitution and the ECHR, which guarantee the right to a fair trial, judicial protection and legal remedy. The second premise, equally unfounded, on which the Constitutional Court based its decision is the belief that the abolition of the objective deadline for reopening of the administrative procedure was necessary in order to enable the removal of the consequences of violations of rights, determined by the Constitutional Court or the ECtHR. By leaving only a subjective deadline, difficult to prove, the level of legal certainty has been lowered. Finally, the ECtHR considered that the existence of a limitless possibility of official removal of final legal acts violated Art. 6 ECHR. This was made possible by the abolition of the objective deadline for reopening of the procedure.
Keywords: Constitutional Court; procedure reopening; Law on General Administrative Procedure